2015
DOI: 10.1016/j.jns.2015.08.158
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the direct cost of epilepsy among Sudanese patients attending charity clinic in Omdurman 2014

Abstract: Background: Epilepsy is a common disease with economic impact in form of frequent clinical visits, investigations and management. Objective: To estimate the direct and part of the indirect costs of epilepsy. Design and methods: The study was performed on a case series of medically treated Sudanese patients with epilepsy in a charity clinic. Data on clinical characteristics, utilization of medical services, and costs were collected from 38 patients using a standardized pre-tested format. The patients' approval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…[22]The same Group made another study to assess the association of medications adherence with the quality of life and cost of epilepsy among Sudanese epilepsy patients attending the charity clinic and they found that Patients with low adherence to antiepileptics are more likely to have lower quality of life. [22] In 2015 Abbashar Hussein, and his colleagues studied the cosmetic effect of Antiepileptic drugs among Sudanese patients attending charity clinic in Omdurman and they conclude that their patients prioritize medication intake in spite of the presence of cosmetic effect, and this together with the absence of association between quality of life and the cosmetic effect may be attributed to different Sudanese patients' perception to these cosmetic effects from other populations in addition to the unique Sudanese culture. [23] Like what was mentioned in the literature our study showed that patients with tertiary education and above had shown a signi cantly high quality of life, education improves the quality of their lives and leads to broad social bene ts to individuals and society.…”
Section: Discussionmentioning
confidence: 99%
“…[22]The same Group made another study to assess the association of medications adherence with the quality of life and cost of epilepsy among Sudanese epilepsy patients attending the charity clinic and they found that Patients with low adherence to antiepileptics are more likely to have lower quality of life. [22] In 2015 Abbashar Hussein, and his colleagues studied the cosmetic effect of Antiepileptic drugs among Sudanese patients attending charity clinic in Omdurman and they conclude that their patients prioritize medication intake in spite of the presence of cosmetic effect, and this together with the absence of association between quality of life and the cosmetic effect may be attributed to different Sudanese patients' perception to these cosmetic effects from other populations in addition to the unique Sudanese culture. [23] Like what was mentioned in the literature our study showed that patients with tertiary education and above had shown a signi cantly high quality of life, education improves the quality of their lives and leads to broad social bene ts to individuals and society.…”
Section: Discussionmentioning
confidence: 99%
“…Insurance rarely helps and patients find themselves forced to sell valuable assets like one's cow or shop to cover the expenses, and many find themselves in debt. All of these factors need to be accounted for by the patient and caregivers and affect adherence negatively [11].…”
Section: Anti-epileptic Drugs (Aeds) In Sudanmentioning
confidence: 99%